Review Of The Psychology Of The Main Character In The Film Hafalan Shalat Delisa By Sony Gaokasak, Study Of Literary Psychology - S, Nofiana; Rahmi, Hayatun; Iqbal, Muhammad (LPPM Universitas PGRI Sumatera Barat, 2025)
This research aims to determine and describe the psychological condition and conflict of the main character in the film Hafalan Salah Delisa by Sony Gaokasak. The method used in this research is descriptive. Descriptive methods are used to explain research data. The data source in this research is the film Hafalan Shalat Delisa by Sonu Gaokasak which was released on December 22 2011. The data in the research are texts or sentences that show psychological conditions and psychological conflicts in the film Hafalan Shalat Delisa by Sony Gaokasak. Data collection in this research was through documentation and observation. The data analysis technique is carried out in three stages, namely, data reduction, data presentation and drawing conclusions. The results of this research are that the psychology of the main character in the film Hafalan Salah Delisa by Sony Gaokasak is (1) lazy, (2) happy, (3) enthusiastic, (4) frustrated, (5) disappointed, and (6) angry. The factors causing the psychological conflict of the main character in the film Hafalan Shalat Delisa by Sony Gaokasak include: (1) personal factors, (2) biological factors in the form of the environment, and (3) social. The consequences arising from the psychological conflict of the main character in the film Hafalan Salah Delisa by Sony Gaokasak are (1) lazy, (2) happy, (3) enthusiastic, (4) frustrated, (5) disappointed, and (6) angry.